A Web-Based Expert System for Pest Diagnosis in Oyster Mushroom Cultivation Using Forward Chaining - Annisa, Annisa; Nasir, Januardi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Oyster mushrooms are one of the most widely cultivated edible mushrooms in Indonesia due to their high economic value and stable market demand. However, during the cultivation process, farmers often face challenges such as pest attacks from ants, centipedes, and snails. These conditions lead to a decrease in both the quality and quantity of the harvest. Farmers' limited knowledge in identifying pests and handling methods is one of the main causes of crop failure. Therefore, this study aims to design and develop a web-based expert system using the forward chaining method to assist farmers in diagnosing pests based on the symptoms observed. The system was developed using the PHP programming language and MySQL database. The forward chaining method is used to perform reasoning from symptoms to conclusions about the type of pest. Testing results show that the system functions as intended and is capable of providing accurate diagnoses and appropriate handling solutions. This system is expected to serve as an efficient alternative solution to improve the productivity of oyster mushroom cultivation.